The effect of using web-based kahoot media on the learning outcomes of grade x students in informatics subject at man and the optimization of instagram social media utilization for increasing sales at aliya cell, maccorawalie village, sidenreng rappang re - Awwalul Mubaraq; Muhammad Rusdi; Andi Riska Andreani Syafaruddin; Haslindah Pratiwi (Universitas Muhammadiyah Enrekang, 2025)
This study focuses on optimizing the use of Instagram social media to increase sales at Aliya Cell, a business engaged in the sale of mobile phones, accessories, prepaid credit, and digital payment services in Sidenreng Rappang Regency. Although social media has great potential as a marketing tool, Aliya Cell faces several challenges such as a lack of engaging content, inconsistent posting frequency, and minimal use of data for marketing strategies. The purpose of this research is to determine effective strategies for utilizing social media to boost sales and to identify existing obstacles. The type and design of the research used is descriptive qualitative, with data collection through interviews, documentation, and observation. This study is expected to provide practical recommendations for Aliya Cell in enhancing brand visibility, customer interaction, and marketing efficiency through Instagram.